Fibroblast Growth Factor 10 in Pancreas Development and Pancreatic Cancer - Ndlovu, Rodrick; Deng, Lian-Cheng; Wu, Jin; Li, Xiao-Kun; Zhang, Jin-San (Frontiers in Genetics, 2018)
The tenacious prevalence of human pancreatic diseases such as diabetes mellitus and adenocarcinoma has prompted huge research interest in better understanding of pancreatic organogenesis. The plethora of signaling pathways involved in pancreas development is activated in a highly coordinated manner to assure unmitigated development and morphogenesis in vertebrates. Therefore, a complex mesenchymal-epithelial signaling network has been implicated to play a pivotal role in organogenesis through its interactions with other germ layers, specifically the endoderm. The Fibroblast Growth Factor Receptor FGFR2-IIIb splicing isoform (FGFR2b) and its high affinity ligand Fibroblast Growth Factor 10 (FGF10) are expressed in the epithelium and mesenchyme, respectively, and therefore are well positioned to transmit mesenchymal to epithelial signaling. FGF10 is a typical paracrine FGF and chiefly mediates biological responses by activating FGFR2b with heparin/heparan sulfate as cofactor. A substantial number of studies using genetically engineered mouse models have demonstrated an essential role of FGF10 in the development of many organs and tissues including the pancreas. During mouse embryonic development, FGF10 signaling is crucial for epithelial cell proliferation, maintenance of progenitor cell fate and branching morphogenesis in the pancreas. FGF10 is also implicated in pancreatic cancer, and that overexpression of FGFR2b is associated with metastatic invasion. A thorough understanding of FGF10 signaling machinery and its crosstalk with other pathways in development and pathological states may provide novel opportunities for pancreatic cancer targeted therapy and regenerative medicine.